Change from above and resistance to change in the early prescriptive pronouncing dictionaries of English - Trapateau, Nicolas; Duchet, Jean-Louis (Adam Mickiewicz University, 2019)
To what extent is it possible to interpret the data of pronouncing dictionaries of the 18th century in sociolinguistic terms? Several answers are provided by resorting to Labov’s concepts of change from above and change from below the level of awareness. A systematic investigation of John Walker’s Critical Pronouncing Dictionary (1791, 1809), the most complete and cumulative of all such dictionaries of the time, makes it possible to show that an orthoepist like Walker often reflects the pressure in favour of change from above for vowel quality and resistance to such a change in matters of stress placement. By preferring analogy to conservative pronunciations due to his bias in favour of a rational pattern, Walker also links analogy to the “vernacular instinct”, promoting variant forms witnessing a change from below. And many other changes under way in his time, which pass unnoticed in the orthoepist’s discourse and transcriptions, properly deserve to be treated as changes from below, thus making his dictionary the common ground for pressures from above and pressures from below. Walker’s prescription is a complex combination of both promotion of, and resistance to pressures from above according to criteria that reflect the ideals of the upper middle class.
Keywords: analogy; change from above; change from below; orthoepy; palatalization; phonological change; pronouncing dictionaries; stress placement; John Walker